LA NUEVA ECONOMÍA Y SUS FORMAS EMPRESARIALES - Begazo Villanueva, José Domingo (2005)
Economics globalization –as a result of the development achieved both in electronics and telecommunication and market freedom– has createde for once in history a new economics model, where innovation is more important than ever thus intellectual work substitutes its physical counterpart inside the dynamics of an unstable and countinous changing process world.